Maqāṣid al-Sharī'ah's Criticism of the Practice of Hybrid Contracts in Islamic Financial Institutions in Indonesia - Abd Rohman; Ach Mus'if; Khoirun Nasik; Indien Winarwati; Dwi Fidhayanti (Universitas Trunojoyo Madura, 2026)
The rapid development of Islamic financial products in Indonesia has increased the use of hybrid contracts (al-'uqūd al-murakkabah), raising concerns over their conformity with the substantive objectives of Islamic law. This study aims to analyze the implementation of hybrid contracts in Islamic financial institutions from the perspective of maqāṣid al-sharī'ah and to formulate a reconstruction of their conceptual framework. This research employs a qualitative approach with a normative-critical method. Data were collected through a literature review of classical Islamic legal sources, contemporary scholarly publications, and relevant Indonesian regulations governing Islamic finance. The findings reveal that the implementation of hybrid contracts remains predominantly driven by a legal-formal approach, emphasizing contractual validity rather than the realization of maqāṣid al-sharī'ah. In many cases, the contractual structures closely resemble conventional financial mechanisms and potentially constitute ḥīlah (legal stratagems), thereby weakening the principles of justice, transparency, and social welfare. The study argues that the current practice has not fully achieved the objectives of Islamic finance, particularly in promoting distributive justice and public benefit (maṣlaḥah). Accordingly, it proposes a maqāṣid-based reconstruction of hybrid contracts that prioritizes substantive justice, transparency, and welfare-oriented financial practices